2019
DOI: 10.1002/app.48202
|View full text |Cite
|
Sign up to set email alerts
|

Foamability and viscosity behavior of extrusion foamed PLA–pulp fiber biocomposites

Abstract: demonstrates the cell morphology of a biocomposite foam. The foam is made from chain extended PLA (polylactic acid) that contains 10% pulp fibers. The foam is produced with extrusion foaming using isobutane as foaming agent. The image is part of research which investigates how pulp fibers and different foaming agents (isobutane and carbon dioxide) affect the foamability and viscosity behavior of PLA in an extrusion foaming process. The research shows that addition of fibers to PLA foam reduces the average cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…3(g and h). 65 The theory behind this phenomenon was that the cellulose acted as a nucleating agent by introducing interfaces where it is more energetically favorable for a bubble to form. 66,67 Additionally, the cellulose provided a kinetic barrier to PLA strand reconguration during bubble growth, thus restricting the expansion of each individual cell.…”
Section: Cellulosementioning
confidence: 99%
“…3(g and h). 65 The theory behind this phenomenon was that the cellulose acted as a nucleating agent by introducing interfaces where it is more energetically favorable for a bubble to form. 66,67 Additionally, the cellulose provided a kinetic barrier to PLA strand reconguration during bubble growth, thus restricting the expansion of each individual cell.…”
Section: Cellulosementioning
confidence: 99%
“…Carbon dioxide is a much smaller molecule than, for example, isobutane and it tends to permeate the cells faster. This effect has been encountered with PLA foams [7]. While gas permeation values of cellulose palmitate are not known, in some cellulose based thermoplastics, permeation of carbon dioxide is higher than that of nitrogen [48].…”
Section: Effect Of Blowing Agentsmentioning
confidence: 99%
“…Blowing agents can be divided into physical and chemical blowing agents depending on the gas production method. Physical blowing agents are, for example, low boiling point organic hydrocarbons (e.g., isobutane and pentane) [ 6 , 7 , 8 ] or inorganic materials (e.g., nitrogen, carbon dioxide, water, and argon) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ] that are added to the polymer matrix as liquid or gas and usually go through a phase change during foaming. Chemical blowing agents (e.g., sodium bicarbonate, citric acid, and azodicarbonamide) [ 14 , 15 , 16 ] produce gaseous products through chemical reactions, usually decomposition upon heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the composites containing 2 wt% E-43, it could be possible that the melt viscosity was low enough to From the findings of Bocz et al [150], it can be assumed that the filler can affect the efficiency of the CE to improve foaming. On the other hand, Rokkonen et al [154] also found that the CE can in turn affect the effects of the blowing agent during the foaming process. Bleached hardwood (birch) Kraft pulp fibers were used as filler at contents of 10 and 20 wt%.…”
Section: Chain Extender Effectsmentioning
confidence: 99%